write them so all the x variables are on one side
0 = -2x^2 + 9x - 4 and 0 = 6x^2 - x - 2
if you can, factor out any common factors (in this case, you can not for either equation)
You could use the quadratic formula or just a little trial and error to factor the equations.
The first one is easy to factor using trial and error
What factors of -2 and -4 would multiply then add up to 9? Factors for -2 are -2, 1, -1, 2 and factors for -4 are -4, 1, -2, 2, -1, 4
Plug any of those combinations in the formula x 0 = (?x+?)(?x+?)
In this case, 0 = (-2x+1)(x-4), then make each paretheses equal to 0 and solve for x (solution: x = 1/2 or 4)
Both equations would probably be more easily solved using the quadratic formula xoxo gothgirl- kk
Please help me to solve these two equations step by step. They are quadratic equations
1).2x^2+9x+4=0
2).5x^2=-7x
2 answers
hope that helps :D